Attainment of the Millennium Development Goal of Poverty Reduction in Nigeria - An Appraisal - Emediegwu, L.E.; Monye-Emina, A. (Ghana Social Science Journal, 2016)
Fifteen years ago, the largest-ever gathering of heads of State and Government, under the aegis of the United Nations (UN), adopted the Millennium Development Goals (MDGs). One of the fundamental objectives of the MDGs is to free countries, especially developing countries, from the poverty trap. Despite the enormous resources and efforts expended by the Nigerian government for the purpose of achieving the MDG1 of halving the proportion of poor persons by 2015, statistics show that no progress has been made. The authors use descriptive analysis to examine how and why Nigeria has been unable to achieve this fundamental goal of poverty eradication. This challenge is connected with the uncoordinated policy actions in areas that MDGs aim to address as well as the problems of poverty, corruption, and focus on election issues etc. The paper recommends that the country will attain the goal of poverty reduction if the government develops and implements pro-people poverty reduction programmes and policies.
Ghana Social Science Journal, 13(1)
Keywords: Millennium Development Goals; Poverty reduction; National Economic Empowerment; Development Strategy; 7-Point Agenda; Corruption